2018
DOI: 10.1136/bmjsem-2018-000355
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability following youth concussion: how do autonomic regulation and concussion symptoms differ over time postinjury?

Abstract: ObjectivesFollowing youth concussion, objective physiological indicators are needed to corroborate changes in subjective clinical measures. The objectives of the current study were to: (1) explore the effect of concussion on heart rate variability (HRV) across days postinjury in youth athletes aged 13–18 years old, compared with healthy age-matched and sex-matched controls and (2) examine the relationship between postconcussion symptom domains (physical, cognitive, fatigue and emotional) and HRV.MethodsProspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Furthermore, a greater HRV during physical exertion was associated with slower cognitive performance as indexed by the reaction time and reaction time variability on the ONB task at the subacute evaluation (RMSSD). These findings corroborate prior research that observed associations between higher HRV and poorer emotional and cognitive symptoms in concussed adolescents [ 35 ]. Recent literature demonstrates that concussed patients may exhibit an inappropriate increase in vagal tone in response to physiological and cognitive stress compared to healthy controls [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, a greater HRV during physical exertion was associated with slower cognitive performance as indexed by the reaction time and reaction time variability on the ONB task at the subacute evaluation (RMSSD). These findings corroborate prior research that observed associations between higher HRV and poorer emotional and cognitive symptoms in concussed adolescents [ 35 ]. Recent literature demonstrates that concussed patients may exhibit an inappropriate increase in vagal tone in response to physiological and cognitive stress compared to healthy controls [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recent evidence has shown that HRV metrics are associated with symptom severity and postinjury deficits in cognitive function following a concussion [ 34 , 35 ]. Although promising, the current literature is incomplete and has not yet examined HRV as a predictive marker of the adolescent concussion outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability may be adequately sensitive to identify effects in short term testing conditions. Changes in HRV analyses are demonstrated following concussion injury in youth [26]. Accordingly, future work should explore the importance of HRV measures and the potential influence of cumulative header impacts on brain health.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of ABN-CBD has been shown to attenuate these effects in rats and even promote vagal responses (such as decreased heart rate and mean arterial pressure), supported by a high frequency increase in the electrocardiogram (ECG) R-R index spectral analysis. 187 It is important to note that heart rate variability impairments have been noted following concussion, 74,188,189 although the specific physiological mechanism(s) is still unknown.…”
Section: Cardiovascular Physiology In Relation To Concussionmentioning
confidence: 99%